Using reflection to improve distance learning course delivery: a case study of teaching a management information systems course. (4th May 2019) - Fathelrahman, Adil
ABSTRACT: Past research has considered the reflective practices of the teacher as an important activity in the learning cycle. Some of it has introduced the term 'reflective teacher', showing that such practice has become increasingly important. This paper discusses literature related to various means of collecting feedback from students, the socio-technical approach to management information systems (MISs) and reflective models. It documents the reflective practices that the author followed while teaching an MIS distance education course. The findings of this research show that actively reflecting on feedback collected from students could improve teaching quality and lead to better understanding for students in future cohorts.